Transfer Payment Systems and Financial Distress: Insights from Health Insurance Premium Subsidies - Christian P. R. Schmid; Nicolas Schreiner; Alois Stutzer (Institute of Labor Economics (IZA), 2020)
How should payment systems of means-tested benefits be designed to improve the financial situation of needy recipients most effectively? We study this question in the context of mandatory health insurance in Switzerland, where recipients initially received either a cash transfer or subsidized insurance premiums (a form of in-kind transfer). A federal reform in 2014 forced cantons (i.e. states) to universally switch to in-kind provision. We exploit this setting based on a difference-in-differences design, analyzing rich individual-level accounting data and applying a machine learning approach to identify cash recipients prior to the reform. We find that switching from cash to in-kind transfers reduces the likelihood of late premiums payments by about 20% and of government debt collection for long-term missed payments by approximately 16%. There is no evidence for a negative spillover effect on the timely payment of the non-subsidized coinsurance bills for health services after the regime change.
Keywords: D14; G52; H24; I13; 330; health insurance; transfers; cash subsidies; in-kind transfers; financial distress; debt collection